2015
DOI: 10.5423/rpd.2015.21.2.082
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characteristics of Acidovorax citrulli Population Causing Bacterial Fruit Blotch against Cucurbits in Korea

Abstract: Acidovorax citrulli, the causal agent of bacterial fruit blotch, has caused an economically destructive damage in cucurbits cultivation fields worldwide. To consider more effective disease management, 33 A. citrulli isolates collected from various cucurbits in Korea were analysed by multi-locus phylogeny using five conserved loci (16S rRNA, adk, gltA, glyA, pilT). Two distinct groups (KCC1 and KCC2) in the population were identified on the base of group-specific genetic variation. Out of them, the predominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…After watermelon, melon is an important fruit crop, with 26 million tons of melons produced global in 2009 (). There are reports of many A. citrulli strains isolated from melon hosts [5,52,61,64,67,68,69]. However, it is not known if these strains are specifically virulent towards melon or more virulent towards them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After watermelon, melon is an important fruit crop, with 26 million tons of melons produced global in 2009 (). There are reports of many A. citrulli strains isolated from melon hosts [5,52,61,64,67,68,69]. However, it is not known if these strains are specifically virulent towards melon or more virulent towards them.…”
Section: Discussionmentioning
confidence: 99%
“…Contrastingly, PCR assays combined with immunological techniques [46,47], immune magnetic separation (IMS) [48], and magnetic capture hybridization [49] additionally used for the detection of A. citrulli strains. These PCR assays were developed to target specific genes, such as 16S rDNA, internal transcribed spacer (ITS) regions, YD-repeat proteins, and hrp genes, which often lack substantial polymorphism between closely related bacterial species and thus may not be suitable for the detection of host-crop-wise virulent A. citrulli strains [50,51,52]. Recently, whole genome sequence of A. citrulli strains were reported in melon [50,53] and watermelon [54,55,56].…”
Section: Introductionmentioning
confidence: 99%
“…immunomagnetic separation (IMS) and magnetic capture hybridization (Amagliani et al 2006) have been applied for detection of A. citrulli strains. These PCR assays were developed to target specific genes such as 16S rDNA, internal transcribed spacer (ITS) regions, hrp genes and YD-repeat proteins, which frequently lack of substantial polymorphism between closely related bacterial species, thus they not suitable for the detection of virulent A. citrulli strains (Eckshtain-Levi et al 2016;Song et al 2018;Slovareva et al 2019).…”
Section: Diagnostic Tools For Identification and Detection Of A Citrullimentioning
confidence: 99%
“…The rep-PCR method has been recommended for characterization of bacteria and rapid method for distinguishing closely related species, subspecies, strains, serotypes, and others (Rampadarath et al 2015;Besler & Little 2017). Numerous studies of have shown the application of rep-PCR using three specific primers, ERIC, BOX and REP to distinguish the strains of A. citrulli from different hosts (Walcott et al 2004;Burdman et al 2005;Choi et al 2015;Song et al 2018). The primers used were BOXA1R primer (5'-CTA CGG CAA GGC GAC GCT GAC G-3') (Walcott et al 2004;Song et al 2018), ERI-C1R (5'-ATGT AAGCTCCTGGGGATTCAC-3') and ERIC2 (5'-AAGT AAGTGACTGGGGT-GAGCG-3') (Choi et al 2015;Song et al 2018),…”
Section: Repetitive Sequence Based Polymerase Chain Reaction (Rep-pcr)mentioning
confidence: 99%
“…valerianellae (Camellia sinensis) (Tomihama , 2006), (Takikawa , 2008). 2011 (Han , 2012), A. valerianellae (Song , 2015). A.…”
Section: (Bacterial Black Spot)mentioning
confidence: 99%